Co-delivery of paclitaxel and melittin by glycopeptide-modified lipodisks for synergistic anti-glioma therapy. Issue 27 (2nd July 2019) - Wang, Huan; Wang, Songli; Wang, Ruifeng; Wang, Xiaoyi; Jiang, Kuan; Xie, Cao; Zhan, Changyou; Wang, Hao; Lu, Weiyue
Abstract : Nanosized lipodisks with flat circular phospholipid bilayers surrounded by PEGylated edges have demonstrated promise in drug delivery. Abstract : Nanosized lipodisks with flat circular phospholipid bilayers surrounded by PEGylated edges have demonstrated promise in drug delivery. In the present work, a lipodisk-based paclitaxel and melittin co-delivery system functionalized with glycopeptide 9 G-A7R ( 9 G-A7R-Disk/PTX/melittin) was successfully constructed, in which melittin which was fully protected from proteolysis and hemolysis was effectively reduced. The ratio of paclitaxel to melittin in lipodisks could be accurately controlled through a film hydration–adsorption method. Paclitaxel combined with melittin showed synergism against U87 cells in vitro, and 9 G-A7R-Disk/PTX/melittin demonstrated an enhanced anti-glioma effect in vivo, significantly prolonging the survival time of glioma-bearing mice. The results suggested a promising formulation for the co-delivery of paclitaxel/melittin and glioma-targeted therapy.